Location-selective work function engineering by self-assembled monolayers - Zhang, Chaoran; Liu, Yangbiao; Tai, Yian; Terfort, Andreas; Zharnikov, Michael (The journal of physical chemistry letters, 2024)
Control over specific interfaces in devices represents a key challenge for modern organic electronics and photovoltaics. Such control is frequently gained by the use of self-assembled monolayers (SAMs), which, by selection of a proper anchoring group, are generally discriminative with respect to different materials but are not selective between different areas of the same material. In particular, selective tailoring of the work function may be useful for different functional devices in a circuit. Here we demonstrate an approach for solving this problem, opening a way to function-selective electrostatic engineering of chemically identical areas, such as source and drain electrodes in a specific type of organic transistor and, more importantly, the electrodes in different types of organic devices, such as p- and n-channel transistors, located on the same circuitry board. The approach is based on the ultraviolet-light-promoted exchange reaction of SAMs on gold, a standard electrode material in organic electronics.
Gesehen am 11.11.2024